A prospective guide for clinical implementation of selected OGTT- derived surrogate indices for the evaluation of β- cell function and insulin sensitivity in patients with transfusion-dependent β- thalassaemia : β-thalassemia and OGTT surrogate indices - De Sanctis, Vincenzo; Soliman, Ashraf T; Daar, Shahina; Tzoulis, Ploutarchos; Karimi, Mehran; Saki, Forough; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2023)
The gold standard for the measurement of insulin secretion is the hyperglycemic clamp and for insulin sensitivity the hyperinsulinemic euglycemic clamp, respectively. A number of surrogate indices, derived from plasma glucose and insulin levels at a fasting state or after oral glucose load, have been proposed to estimate β-cell response, and the ability of β-cells to compensate for changes of insulin sensitivity by modulating insulin secretion (disposition index). Starting from the current recommendations for the annual screening of glucose dysregulation in patients with transfusion dependent β-thalassemia (β-TDT), this article summarizes the most frequently used indirect indices of insulin secretion and resistance derived from the oral glucose tolerance test (OGTT) and discusses the strengths and weaknesses of selected indices and the basic concepts underlying each method for the appropriate evaluation of glucose regulation. Basal indices for β-cell function and insulin sensitivity, albeit simple and cheap, have limited usefulness due to a high coefficient variation and the lack of data about response to glucose load. Therefore, measurement of indices during an OGTT, despite being costly and time-consuming, is suggested since it can detect, even subtle, dynamic changes in insulin secretion and glucose handling. In patients with β-TDT, the indices derived from OGTT may offer an additional factor to evaluate the efficiency of iron chelation therapy and detect patients who may need intensification of iron chelation therapy and/or pharmacological intervention.